Combining `dry' co‐crystallization and in situ diffraction to facilitate ligand screening by X‐ray crystallography. (1st August 2015) - Gelin, Muriel; Delfosse, Vanessa; Allemand, Frédéric; Hoh, François; Sallaz‐Damaz, Yoann; Pirocchi, Michel; Bourguet, William; Ferrer, Jean‐Luc; Labesse, Gilles; Guichou, Jean‐François
<x xml:space="preserve">Abstract</x> X‐ray crystallography is an established technique for ligand screening in fragment‐based drug‐design projects, but the required manual handling steps – soaking crystals with ligand and the subsequent harvesting – are tedious and limit the throughput of the process. Here, an alternative approach is reported: crystallization plates are pre‐coated with potential binders prior to protein crystallization and X‐ray diffraction is performed directly `in situ' (or in‐plate). Its performance is demonstrated on distinct and relevant therapeutic targets currently being studied for ligand screening by X‐ray crystallography using either a bending‐magnet beamline or a rotating‐anode generator. The possibility of using DMSO stock solutions of the ligands to be coated opens up a route to screening most chemical libraries.